2020
DOI: 10.1016/j.bpj.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

A Bistable Mechanism Mediated by Integrins Controls Mechanotaxis of Leukocytes

Abstract: Recruitment of leukocytes from blood vessels to inflamed zones is guided by biochemical and mechanical stimuli, with mechanisms only partially deciphered. Here, we studied the guidance by flow of primary human effector T lymphocytes crawling on substrates coated with ligands of integrins LFA-1 (L2) and VLA-4 (41). We reveal that cells segregate in two populations of opposite orientation for combined adhesion, and show that decisions of orientation rely on a bistable mechanism between LFA-1-mediated upstrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 56 publications
10
35
1
Order By: Relevance
“…In contrast, T cells migrating on VCAM-1 showed less contact with the stimulatory surface and seem to adhere mostly through the center and uropod of the cell (Fig 2E-F). This morphology is consistent with observations by others (14,15). Analysis of the movies revealed that while T cells migrating on ICAM-1 coated surfaces moved smoothly, showing sustained actin polymerization at the leading edge, T cells on VCAM-1 had periodic bursts of movement concomitant with brief actin flares at the front of the cell (Fig 2F-G, see Supplemental Movies 1 and 2).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, T cells migrating on VCAM-1 showed less contact with the stimulatory surface and seem to adhere mostly through the center and uropod of the cell (Fig 2E-F). This morphology is consistent with observations by others (14,15). Analysis of the movies revealed that while T cells migrating on ICAM-1 coated surfaces moved smoothly, showing sustained actin polymerization at the leading edge, T cells on VCAM-1 had periodic bursts of movement concomitant with brief actin flares at the front of the cell (Fig 2F-G, see Supplemental Movies 1 and 2).…”
Section: Resultssupporting
confidence: 90%
“…We and others have previously shown that T cells preferentially migrate against the direction of shear on ICAM-1 and with the direction of shear on VCAM-1 (11)(12)(13)(14)(15)(16)(17). To verify that our primary mouse T cells display this behavior, we activated T cells for two days and rested them for an additional three days in the presence of IL-2, a procedure that generates highly motile T cell blasts expressing both LFA-1 and VLA-4.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 superimposes transmission images to localize cell body (grey), fluorescence microscopy images of the patterned stripes (red) and RICM images of the cell adhesion footprint (green). On homogeneously adherent substrates (Figure 3-A,D) , cells display adherent lamellipods and non-adherent rear on ICAM-1, and conversely adherent rear and detached lamellipods on VCAM-1, as previously described (28). On substrates with adherent and non-adherent stripes (Figure 3-B,E), adhesion (green) signal was bright on integrin-ligand stripes (bright red) and extinct on anti-adhesive stripes (light red), which confirms that cells crawl on adherent stripes and swim over non-adherent stripes.…”
Section: Lymphocytes Display Integrin-mediated Haptotaxis On Globallysupporting
confidence: 76%
“…Residual fluorescent intensity due to adsorbed antibodies was measured and then subtracted from the previous measurements. Previous study (28) showed a linear relation between the fluorescent intensity and the bulk concentration. We assume that the signal is given by the total number of molecules in the thin channel, then the volume concentration can be converted to a surface concentration for a channel of 41 µm in height.…”
Section: Fluorescent Quantification Of Adhesion Moleculesmentioning
confidence: 79%
See 1 more Smart Citation